2000
DOI: 10.1002/(sici)1098-2396(200001)35:1<26::aid-syn4>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrodiffusion of synaptic receptors: a mechanism to modify synaptic efficacy?

Abstract: We analysed physical forces that act on synaptic receptor-channels following the release of neurotransmitter. These forces are: 1) electrostatic interaction between receptors, 2) stochastic Brownian diffusion in the membrane, 3) transient electric field force generated by currents through open channels, 4) viscous drag force elicited by the flowing molecules and 5) strong in-membrane friction. By considering alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) type receptors, we show that, depending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Another important implementation follows from the inhomogeneity of the intracleft voltage, indicating a significant voltage gradient between inner parts and the edge of the synaptic contact. The gradients estimated from the contact dimensions and the voltages in our model (ϳ10 4 V/m) are sufficiently high to cause an electrophoretic drift of charged molecules within the cleft (Savtchenko et al, 1999). In the excitatory synaptic contacts, like those considered in this study, negatively charged molecules should be electrophoretically pushed out of the cleft and positively charged ones should be drawn into the cleft.…”
Section: Biological Implementationsmentioning
confidence: 82%
“…Another important implementation follows from the inhomogeneity of the intracleft voltage, indicating a significant voltage gradient between inner parts and the edge of the synaptic contact. The gradients estimated from the contact dimensions and the voltages in our model (ϳ10 4 V/m) are sufficiently high to cause an electrophoretic drift of charged molecules within the cleft (Savtchenko et al, 1999). In the excitatory synaptic contacts, like those considered in this study, negatively charged molecules should be electrophoretically pushed out of the cleft and positively charged ones should be drawn into the cleft.…”
Section: Biological Implementationsmentioning
confidence: 82%
“…As can be seen from Figure 3 some of the spikes measured at the output of the later circuit are delayed or shifted compared to the ones measured at the output of the former circuit. This shift can also be linked to the assumption that Sialylation (Sialic acid) could cause a large depolarising shift in the activation curve [15] of voltage-gated sodium channels which consequently alter the spiking threshold of the neuron without any alteration in the patch-clamp recorded membrane voltage Vm in hippocampal pyramidal neurons [16].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical systematic models introduced for amyloid channel-like structures and Alphasynuclein based highly conductive ion channels [15] also do support these ion channellike structures. It has been shown that Sialylation (Sialic acid) can cause a large depolarising shift in the activation mechanism [16] of voltage-gated sodium channels and so altering the spiking threshold of the neuron without any variation in the patch-clamp recorded membrane voltage Vm in hippocampal pyramidal neurons [17]. Now, the issue is that could these small peptides, which can only partly infuse membrane, have the potential of formation of ionic amyloid channel models.…”
Section: Doi: 1024012/dumf703270mentioning
confidence: 99%